2023
DOI: 10.1242/dev.202078
|View full text |Cite
|
Sign up to set email alerts
|

Region-specific reversal of epidermal planar polarity in the rosette fancy mouse

Maureen Cetera,
Rishabh Sharan,
Gabriela Hayward-Lara
et al.

Abstract: The planar cell polarity (PCP) pathway collectively orients cells with respect to a body axis. Hair follicles of the murine epidermis provide a striking readout of PCP activity in their uniform alignment across the skin. Here, we characterize, from the molecular to tissue-scale, PCP establishment in the fancy rosette mouse, a natural variant with posterior-specific whorls in its fur, to understand how epidermal polarity is coordinated across the tissue. We find rosette hair follicles emerge with reversed orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…Loss or ectopic activation of PCP signalling is deleterious for normal tubular architecture, implying that cell-intrinsic levels of PCP components are critical for correct tissue patterning. In normal mammalian development, PCP proteins (including CELSR, VANGL and FZD, for example) asymmetrically localise along the proximal-distal axis of cells thereby imparting spatial information across a population of cells perpendicular to the apico-basal cell axis 13,14 . Indeed, evidence from zebrafish demonstrated that targeting PCP components pk1a , vangl2 or ankrd6 affects the development of a complex biliary tree 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Loss or ectopic activation of PCP signalling is deleterious for normal tubular architecture, implying that cell-intrinsic levels of PCP components are critical for correct tissue patterning. In normal mammalian development, PCP proteins (including CELSR, VANGL and FZD, for example) asymmetrically localise along the proximal-distal axis of cells thereby imparting spatial information across a population of cells perpendicular to the apico-basal cell axis 13,14 . Indeed, evidence from zebrafish demonstrated that targeting PCP components pk1a , vangl2 or ankrd6 affects the development of a complex biliary tree 15 .…”
Section: Introductionmentioning
confidence: 99%